2020
DOI: 10.5812/amh.99131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endurance Training with Saffron Consumption on PGC1-α Gene Expression in Hippocampus Tissue of Rats with Alzheimer’s Disease

Abstract: Background: Alzheimer's disease (AD) is a type of cognitive impairment that disrupts the mitochondrial function and metabolism of neurons. Studies have shown that training is a potent factor in enhancing mitochondrial biogenesis and saffron with its antioxidant properties can improve neurodegenerative disorders effectively. Objectives: Accordingly, the aim of this study was to investigate the effect of endurance training (ET) with saffron consumption on peroxisome proliferator-activated receptor-γ coactivator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…5,9,11,20 Furthermore, Sa plant, with enzymatic and non-enzymatic antioxidant mechanisms, reduces NF-κB, IL-1, and TNF-alpha, increases BDNF, CREB, and VGF, regulates calcium channels, activates calcium-calmodulin and FOXO, improves neurotransmitters functions, regulates cell ion function, and increases PGC1-α, mitochondrial biogenesis, insulin sensitivity and weight loss. 25,26,28 Due to changes in heart weight and heart weight to body weight ratio, which require more pathological and physiological examination, one of the limitations of the present study is the lack of examination of pathological changes in the heart. Therefore, it is suggested that pathological examination be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…5,9,11,20 Furthermore, Sa plant, with enzymatic and non-enzymatic antioxidant mechanisms, reduces NF-κB, IL-1, and TNF-alpha, increases BDNF, CREB, and VGF, regulates calcium channels, activates calcium-calmodulin and FOXO, improves neurotransmitters functions, regulates cell ion function, and increases PGC1-α, mitochondrial biogenesis, insulin sensitivity and weight loss. 25,26,28 Due to changes in heart weight and heart weight to body weight ratio, which require more pathological and physiological examination, one of the limitations of the present study is the lack of examination of pathological changes in the heart. Therefore, it is suggested that pathological examination be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…25 In addition, aerobic training and crocin consumption increased PGC1-α gene expression level in the hippocampus and increased aerobic capacity in rats with AD. 13,26 However, interval and continuous training along with crocin consumption did not have an interactive effect on calorie intake in rats with type 2 diabetes but it caused weight loss. 27 Exercise training, depending on the type and intensity of activity, has different effects on the biological pathways of the cell.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AD (Alzheimer's disease) is the most common form of dementia among the elderly [1]. Systematically, it is characterized by the impairment of memory and other intellectual abilities to such an extent that it affects the daily functioning of life.…”
Section: Introductionmentioning
confidence: 99%